2019
DOI: 10.1182/blood-2018-03-785915
|View full text |Cite
|
Sign up to set email alerts
|

How I treat MDS after hypomethylating agent failure

Abstract: Hypomethylating agents (HMA) azacitidine and decitabine are standard of care for myelodysplastic syndrome (MDS). Response to these agents occurs in ∼50% of treated patients, and duration of response, although variable, is transient. Prediction of response to HMAs is possible with clinical and molecular parameters, but alternative approved treatments are not available, and in the case of HMA failure, there are no standard therapeutic opportunities. It is important to develop a reasoned choice of therapy after H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 86 publications
2
49
0
1
Order By: Relevance
“…e response rate is approximately 50% in treated patients; however, the duration of response is transient, and HMAtreated MDS patients eventually lose responsiveness. For MDS patients with HMA treatment failure, standard therapeutic opportunities are few [18]. Our study showed that CM treatment may be a good choice for MDS patients.…”
Section: Discussionmentioning
confidence: 72%
“…e response rate is approximately 50% in treated patients; however, the duration of response is transient, and HMAtreated MDS patients eventually lose responsiveness. For MDS patients with HMA treatment failure, standard therapeutic opportunities are few [18]. Our study showed that CM treatment may be a good choice for MDS patients.…”
Section: Discussionmentioning
confidence: 72%
“…The patient responded well to azacitidine with good quality of life and presented an optimal hematological control for over two years. The poor prognosis and the very dismal outcome [13,14] after azacitidine-failure are unfortunately currently unmet challenges for which no approved treatments as well as no standard therapeutic opportunities are available [14]. In our case, the coincidence of AML progression and CLL onset suggested the use of the BCL2 inhibitor venetoclax [15,16].…”
Section: Letter To the Editormentioning
confidence: 83%
“…While HMA therapy is approved only for IPSS higher-risk MDS patients in Europe, AZA and DEC are approved for the treatment of all patients with MDS in the US. 17 The National Comprehensive Cancer Network (NCCN) is recommending HMA use primarily for patients with intermediate- or high-risk MDS who are not candidates for intensive therapy, who are unlikely to respond to other treatment modalities (e.g., immunosuppressive therapy), or as a bridge to allo-SCT. 8 …”
Section: Hypomethylating Agents In Mds Treatmentmentioning
confidence: 99%
“…Various expert recommendations have been published recently. 17 , 38 Furthermore, novel agents in MDS therapy have often been extrapolated from active agents for the treatment of AML. While both disorders are related, the direct applicability of AML study results to MDS patient cohorts cannot be assumed.…”
Section: Treatment Options For the Hma Resistant Patientmentioning
confidence: 99%
See 1 more Smart Citation